Design of the Attendance System using RFID and Similarity Metric Learning at Universitas Dinamika Bangsa - Toscany, Afrizal; Rahim, Abdul; Bustami, Irwan; Sadikin, Ali (AI Society & STMIK Indonesia, 2022)
Admission of new students at Universitas Dinamika Bangsa has a significant increase, so that the number of active students on campus becomes more. This has an impact on the recapitulation process of lecture absence by study staff to be longer than before, due to the calculation process that is done manually. This research will create a system designed to increase efficiency in lecture attendance activities by presenting an attendance system equipped with an RFID (Radio Frequency Identification) Reader and camera. In addition to the process of digitization of attendance data will be added similiarity metric learning method for validation of student absences that are done periodically. The method to be used in system development is prototyping. This research resulted in a system design with UML modeling and absentee device design.